2008
DOI: 10.3945/jn.108.093633
|View full text |Cite
|
Sign up to set email alerts
|

Energy Restriction Impairs Natural Killer Cell Function and Increases the Severity of Influenza Infection in Young Adult Male C57BL/6 Mice

Abstract: Energy restriction (ER) without malnutrition extends lifespan in mice and postpones age-related changes in immunity. However, we have previously shown that aged (22 mo old) ER mice exhibit increased mortality, impaired viral clearance, and reduced natural killer (NK) cell cytotoxicity following influenza infection compared with aged mice that consumed food ad libitum (AL). To determine whether the detrimental effects of ER in response to influenza infection occur independently of advanced age, young adult (6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 34 publications
0
67
1
Order By: Relevance
“…Effros et al imposed ip injections of influenza virus, while the Gardner studies used an intranasal route of administration which was more consistent with the typical route of infection (Gardner et al, 2011). Gardner et al noted decreased survival of aged (22 mo) B6 mice on lifelong 40% CR following infection (Gardner, 2005), and Ritz et al (2008) noted the same even in young (6 mo) B6 mice on CR(Ritz et al, 2008). Both studies observed decreased natural killer (NK) cell activity in lungs of CR mice.…”
Section: Are There Detrimental Effects Of Cr?mentioning
confidence: 99%
“…Effros et al imposed ip injections of influenza virus, while the Gardner studies used an intranasal route of administration which was more consistent with the typical route of infection (Gardner et al, 2011). Gardner et al noted decreased survival of aged (22 mo) B6 mice on lifelong 40% CR following infection (Gardner, 2005), and Ritz et al (2008) noted the same even in young (6 mo) B6 mice on CR(Ritz et al, 2008). Both studies observed decreased natural killer (NK) cell activity in lungs of CR mice.…”
Section: Are There Detrimental Effects Of Cr?mentioning
confidence: 99%
“…Several decades ago, Weindruch et al (12) reported that CR resulted in decreased splenic NK cell cytotoxicity compared with aged matched controls, although this could be ameliorated by polyinosinic:polycytidylic acid. More recently, we have shown CR results in increased susceptibility to primary influenza infection and decreased influenza-induced NK cell cytotoxicity in young and aged mice (13, 14). This was accompanied by the observation that NK cell numbers and frequency are decreased in the spleen of young CR mice (14).…”
mentioning
confidence: 99%
“…On one hand, CR apparently attenuates age-related decline in the immune system of rodents (delayed immune-senescence) (Kristan, 2008;Pahlavani, 2004). On the other, studies using bacteria (Sun, Muthukumar, Lawrence et al, 2001), viruses (Gardner, 2005;Ritz and Gardner, 2006;Ritz, Aktan, Nogusa et al, 2008) and parasites (Kristan 2007) showed a significantly reduced capacity of long-term CR rodents to respond to and to survive such infections despite their better immune system. This happened because the response of the immune system to an infectious pathogen is very expensive in terms of energy and the body of CR rodents may fail to mobilize the energy needed (Ritz and Gardner, 2006).…”
Section: Comparing Our Results With the Outcomes Of The Calorie Restrmentioning
confidence: 99%